Improving the Eleventh Grade Students’ Reading Comprehension by Using Discussion Web Strategy in Analytical Exposition Text - Estiningtyas, Asri (ELLITE, 2017)
This research aimed to know whether Discussion Web strategy can improve theeleventh grade students’ reading comprehension in analytical exposition text andparticipation at MA Al-Badri Kalisat in 2017/2018 academic year or not. Thetype of this research was Classroom Action Research (CAR). This research wasdone in two cycles which consisted of planning, implementing, observing, andreflecting in each cycle. The subject of this research was the students of ElevenScience at MA Al Badri Kalisat totaling 18 students. The research instruments used were reading test and observation checklist of the students’ participation.Based on the research result, the result of students’ reading test was 44.5% andstudents’ participation was 52.75% in cycle 1. Then, the research was continuedto the cycle 2 by modifying the teaching and learning activity and revisingthe lesson plan. The improvement occurred in cycle 2. The students’ readingtest was 77.78% and students’ participation was 80.55%. Therefore, it could beconcluded that the Discussion Web strategy can improve the eleventh gradestudents’ reading comprehension and participation at MA Al-Badri Kalisat inthe 2017/2018 academic year.